1977
DOI: 10.1017/s0021859600061542
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sward characteristics on the herbage intake of grazing calves

Abstract: Experiments were carried out at the Grassland Research Institute, U.K. (Expt 1) and the Universidad Central de Venezuela, Maracay (Expt 2), to study the influence of sward characteristics upon the herbage intake of young grazing cattle. In both studies the animals were strip-grazed in small groups on a series of plots, at a generous herbage allowance.The digestibility of the herbage ingested exerted a dominant influence on herbage organic matter (OM) intake, which increased at a constant rate as organic matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
86
2
12

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 20 publications
12
86
2
12
Order By: Relevance
“…Table 1 -Body weight and body condition score (scale of 1 to 5) at calving, at the end of the evaluation period, and daily weight variation in the pre-and post-calving periods pastures in the present study, and observed that cows presented better body condition score at calving than those grazing on natural pastures with higher availability (2,500 and 3,000 kg DM/ha), where selective grazing is possible (Hodgson, 1981). Under similar conditions, Lobato et al (1998b) also determined higher pre-calving weight gain in primiparous cows grazing on improved pastures as compared to those on natural pastures.…”
Section: Resultssupporting
confidence: 55%
“…Table 1 -Body weight and body condition score (scale of 1 to 5) at calving, at the end of the evaluation period, and daily weight variation in the pre-and post-calving periods pastures in the present study, and observed that cows presented better body condition score at calving than those grazing on natural pastures with higher availability (2,500 and 3,000 kg DM/ha), where selective grazing is possible (Hodgson, 1981). Under similar conditions, Lobato et al (1998b) also determined higher pre-calving weight gain in primiparous cows grazing on improved pastures as compared to those on natural pastures.…”
Section: Resultssupporting
confidence: 55%
“…Mesmo com o comportamento quadrático da oferta de lâmina foliar, os valores dessa variável no início e final de utilização da pastagem ainda mantiveram-se acima de 2,7 kg de matéria seca/kg de peso corporal, que corresponde ao consumo potencial de matéria seca por novilhas de corte com 18 meses de idade (NRC, 1996). 10 minutos, durante o período diurno, sempre que o animal estivesse em atividade de pastejo, para calcular a taxa de bocado/minuto (Hodgson, 1982), cujo valor multiplicado pelo tempo de pastejo, resultou no número diário estimado de bocados. Para o cálculo da massa do bocado, dividiu-se o consumo de estimado de forragem pelo número diário de bocados (Jamieson & Hodgson, 1979).…”
Section: Resultsunclassified
“…The latter in turn is influenced by selectivity of the animals. However, the extent of selection is associated significantly to the influence of grazing management on canopy structure (Hodgson, 1982). In the present study intake and growth rate of lambs differed significantly between pasture species.…”
Section: Resultsmentioning
confidence: 46%